The Correlation between Technological Devices and Aphasiac People to Enhance Language Communication - Atyaf Hasan Ibrahim; Fatima Rahim Abdulhussein (Intensive Journal, 2020)
Language is a medium of communication that is pivotal to daily life interaction, any disability in using it, including aphasia, causes frustration, feeling lonely, isolation, and alienation due to fear of rejection. Many ways can be used in the treatment of speech and language disorders, such as smartphones and laptops. This study aims at investigating the use of technological devices such as computers and smartphone apps and programs by people with aphasia to enhance communication and enable them to produce and understand spoken and written language. It also aims at stating the age group that most use these technological devices. The researchers built a questionnaire of ten questions concerning which age category is aphasic and which type of major and secondary technological programs and apps are used by them to facilitate communication. Based on the results gained from the questionnaire, the researchers found that the highest range of aphasic people are 45-55 years old, while the lowest are 15-25 years old. Applications of smart phones and computers are widely and effectively used by aphasiac, in addition to social media, in facilitating their communications especially the spoken skills.